2018
DOI: 10.1016/j.jprot.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe and Mn deficiencies on the protein profiles of tomato ( Solanum lycopersicum ) xylem sap as revealed by shotgun analyses

Abstract: The aim of this work was to study the effects of Fe and Mn deficiencies on the xylem sap proteome of tomato using a shotgun proteomic approach, with the final goal of elucidating plant response mechanisms to these stresses. This approach yielded 643 proteins reliably identified and quantified with 70% of them predicted as secretory. Iron and Mn deficiencies caused statistically significant and biologically relevant abundance changes in 119 and 118 xylem sap proteins, respectively. In both deficiencies, metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 98 publications
5
20
0
Order By: Relevance
“…The proteomic approach used in this study identified and quantified 672 proteins in the xylem sap of Brassica napus , which is considerably higher than the 69 proteins previously identified in 2-DE [6], though a recent study found 643 proteins in tomato xylem sap using a similar shotgun method [25], indicating that the shotgun label-free analysis used in this study is very sensitive. Our results showed that nearly 67% of the identified xylem proteins were classified as secretory and 33% were identified as non-secretory, which could in part be due to cytoplasmic contamination.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The proteomic approach used in this study identified and quantified 672 proteins in the xylem sap of Brassica napus , which is considerably higher than the 69 proteins previously identified in 2-DE [6], though a recent study found 643 proteins in tomato xylem sap using a similar shotgun method [25], indicating that the shotgun label-free analysis used in this study is very sensitive. Our results showed that nearly 67% of the identified xylem proteins were classified as secretory and 33% were identified as non-secretory, which could in part be due to cytoplasmic contamination.…”
Section: Discussionmentioning
confidence: 79%
“…At 2 weeks of age, the hydroponically grown Brassica napus seedlings were exposed to 0 (control) and 10 μM Cd (treatment) for 3 days, then xylem sap samples were collected. Briefly, stems were cut with a razor blade 2–3 cm above the basal stems to collect xylem sap for 2 h. Xylem sap from the first 10 min was discarded to avoid contamination from damaged cells as described previously [25]. Xylem sap collected from 24 plants was pooled into one replicate, and a total of three replicates from 72 plants were used for each treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of Col-0 and sec24c were sown in soil and watered with Hoagland nutrient solution weekly. When they were 4 weeks old, the seedlings were exposed to 0 (control) or 20 μM Cd (treatment) for 4 days, after which xylem sap samples were then collected according to a previous method 43 . Brie y, stems were cut with a razor blade 2-3 cm above the basal stems to collect xylem sap during a 2-h period.…”
Section: Xylem Sap Collectionmentioning
confidence: 99%
“…Proteomic approaches, either gel (2-DE) or non-gel-based, are powerful tools to understand the responses that plants elicit when facing metal stresses [ 41 , 42 ]. The xylem sap proteome is expected to reflect changes in plant metabolism upon excess Mn and could also be an essential key for understanding Mn homeostasis.…”
Section: Introductionmentioning
confidence: 99%